2013
DOI: 10.4103/0974-2700.120365
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cervical spine injury among patients with traumatic brain injury

Abstract: Background:Diagnosis of cervical spine injury (CSI) is difficult in patients with an altered level of consciousness as a result of a traumatic brain injury (TBI). Patients with TBI and older adults are at increased risk for CSI. This study examined the various risk factors for CSI among trauma patients with TBI and whether adults who were older (≥55 years) were at higher risk for CSI when they sustained a fall-related TBI.Materials and Methods:Data used was the 2007 National Trauma Data Bank (NTDB), National S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 22 publications
2
29
1
2
Order By: Relevance
“…17,25,27,32,37,42,52 Reported rates of cervical spine injury concomitant with traumatic coma are between 6% and 9%. Lower rates have been cited in reports that detail less precisely the severity of the TBI and the methods of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…17,25,27,32,37,42,52 Reported rates of cervical spine injury concomitant with traumatic coma are between 6% and 9%. Lower rates have been cited in reports that detail less precisely the severity of the TBI and the methods of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Examining subgroups of studies that reported the prevalence in patients with GCS 3-12 and GCS less than or equal to 8 did not reduce the heterogeneity. However, four studies reported the prevalence of concomitant cervical spinal injury in patients with TBI or head injury injured in a motor vehicle accident (MVA) [2,15,21,41]. The I 2 statistic indicated that there was only moderate heterogeneity between these studies (I 2 = 51.44%; 95% CI 0.00-83.95%).…”
Section: Cervical Spinal Injury In Tbimentioning
confidence: 99%
“…Eleven publications reported the prevalence of concomitant cervical spinal injury in patients with a TBI [2,12,15,21,27,28,30,33,34,37,41]. The total sample size including all studies reporting this prevalence is 573,870 patients, with sample sizes of individual studies ranging from 265 [37] to 334,864 [28].…”
Section: Cervical Spinal Injury In Tbimentioning
confidence: 99%
See 2 more Smart Citations